The Effectiveness of Monetary Policy in Small Open Economies : An Empirical Investigation - Primus, Keyra (IMF Working Papers; Working Paper, 2016)
This paper examines the relative effectiveness of the use of indirect and direct monetary policy instruments in Barbados, Jamaica and Trinidad and Tobago, by estimating a restricted Vector Autoregressive model with Exogenous Variables (VARX). The study assumes that the central bank conducts monetary policy using a Taylor-type rule and it evaluates the effects of a reserve requirement policy. The results show that although a positive shock to the policy interest rate has a direct effect on commercial banks' interest rates, there is a weak transmission to the real variables. Furthermore, an increase in the required reserve ratio is successful in reducing private sector credit and excess reserves, while at the same time alleviating pressures on the exchange rate. The findings therefore indicate that central banks in small open economies should consider using reserve requirements as a complement to interest rate policy, to achieve their macroeconomic objectives.